2022
DOI: 10.3390/nu14194032
|View full text |Cite
|
Sign up to set email alerts
|

The Performances of SNAQ, GLIM, mNICE, and ASPEN for Identification of Neurocritically Ill Patients at High Risk of Developing Refeeding Syndrome

Abstract: We previously found that neurocritically ill patients are prone to refeeding syndrome (RFS), a potentially life-threatening complication. However, there is no unified or validated consensus on the screening tool for RFS so far. We aimed to validate and compare the performance of four screening tools for RFS in neurocritically ill patients. We conducted a single-center, observational, retrospective cohort study among neurocritically ill adult patients who were admitted to the neurocritical care unit (NCU), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A recent observational, retrospective cohort study published in 2022 by Liu et al [ 21 ] compared various screening tools, including the American Society for Parenteral and Enteral Nutrition (ASPEN) and modified NICE, and found that the ASPEN criteria had the highest sensitivity and area under the receiver operating characteristic curve at 53.6% and 0.597, respectively. Their guidelines were published in 2020 when an interdisciplinary group worked on consolidating the heterogeneous literature surrounding RFS into a unified clinical definition as well as an updated risk assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…A recent observational, retrospective cohort study published in 2022 by Liu et al [ 21 ] compared various screening tools, including the American Society for Parenteral and Enteral Nutrition (ASPEN) and modified NICE, and found that the ASPEN criteria had the highest sensitivity and area under the receiver operating characteristic curve at 53.6% and 0.597, respectively. Their guidelines were published in 2020 when an interdisciplinary group worked on consolidating the heterogeneous literature surrounding RFS into a unified clinical definition as well as an updated risk assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the attempt to evaluate more accurately the malnourished state, a few studies showed the 2020 ASPEN criteria were not suitable for identification of refeeding risks in critically ill patients. In a retrospective study of neurocritically ill patients, Liu et al [28] compared the performances of 4 tools for assessment of refeeding risks, the Short Nutritional Assessment Questionnaire, the Global Leadership Initiative on Malnutrition (GLIM), the modified criteria of Britain's National Institute for Health and Care Excellence (mNICE), and the ASPEN scales. All 4 tools showed low areas under the receiver operating characteristic curve (AUCs)<0.6.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Evaluating this definition of RFS among ICU patients who were newly initiated on enteral feeding, Adika et al found that RFS occurred in 25%-90% of patients and did not associate with death or other adverse outcomes, 6 suggesting that alternative definitions for RFS should be considered. 4,[6][7][8][9] The objective of this study was to evaluate and compare the performance of various a priori definitions for RFS, including the ASPEN definition, within a single retrospective cohort. We aimed to determine whether different operationalizations of RFS were associated with death or other adverse patient-centered clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…RFS has been operationalized by the American Society for Parenteral and Enteral Nutrition (ASPEN) Parenteral Nutrition Safety Committee's 2020 guidelines as “a decrease in any 1, 2, or 3 of serum phosphorus, potassium, and/or magnesium levels by 10%–20% (mild), 20%–30% (moderate), or >30% and/or organ dysfunction resulting from a decrease in any of these and/or due to thiamin deficiency (severe), occurring within five days of reintroduction of calories.” 1 These ASPEN guidelines were provided so that a unifying set of criteria could guide standardization in research and incidence measurement, with the expectation that this definition could then be refined based on further studies. Evaluating this definition of RFS among ICU patients who were newly initiated on enteral feeding, Adika et al found that RFS occurred in 25%–90% of patients and did not associate with death or other adverse outcomes, 6 suggesting that alternative definitions for RFS should be considered 4,6–9 …”
Section: Introductionmentioning
confidence: 99%